IMPLEMENTASI SISTEM USABILITY SCALE DALAM EVALUASI PERSPEKTIF PENGGUNA TERHADAP SISTEM INFORMASI AKADEMIK BERBASIS MOBILE - Tujni, Baibul; Syakti, Firamon (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
Bina Darma University is one of the higher education institutions in South Sumatra Province. Bina Darma University has made a real contribution in the world of Education, especially in the South Sumatra Province. To ensure the smooth running of the academic routine, Bina Darma University has a special directorate, namely The Directorate of Systems and Information Technology (DSTI). The directorate's main task is to ensure the availability of IT services to support academic activities. One of the services currently available is a mobile-based academic information system (UBD on your hand). Where this service is a development service from an existing web-based academic information system. But to ensure that the service remains well-established, it is necessary to know how the user's perspective on an IT service such as the UBD application on your hand. To find out how far the user is using usability techniques using the system usability scale approach as a measurement tool. The measurement results obtained an average value of 87.2 indicating that the mobile-based academic information system (UBD on your hand) was viewed from an adjective rating including excellence category, seen from the grade scale including group B, and in terms of acceptability including acceptable groups. Thus, the category can be accepted by the user and feasible to use without repairs.